The effect of taping on pain-related somatosensory evoked potentials (pSEPs) - Yamazaki, Yudai; Sato, Daisuke; Maruyama, Atsuo; Yamashiro, Koya; Nakazawa, Sho; Shimojo, Hirofumi; Onishi, Hideaki (Japanese Journal of Physical Fitness and Sports Medicine, 2016)
Taping is widely used in sports medicine to prevent injury, protect affected sites post injury and relieve pain. However, it is not clear whether taping affects the perception of noxious stimulation because in previous studies, it was difficult to selectively activate Aδ fibers. A recently developed, useful, new tool named intra-epidermal electrical stimulation (IES) can preferentially activate Aδ fibers. We aimed to clarify the effect of taping on pain-related somatosensory evoked potentials (pSEPs) using IES. We recorded pSEPs following IES of the right medial forearm in twelve healthy volunteers. pSEPs were recorded from 9 electrodes on the scalp under control, elastic-taping and white-taping conditions. Under the control condition, subjects relaxed on a comfortable reclining seat without taping, whereas under the taping conditions, they were subjected to taping along the forearm with tension (elastic-taping) and without tension (white-taping). Subjects were asked to assign a visual analog scale (VAS) score after each session. The peak amplitudes of N2-P2 were significantly lower under the elastic-taping and white-taping conditions than those under the control condition. VAS was significantly lower elastic-taping condition than those under the control and white-taping conditions. Moreover, there was a significant positive correlation between the amplitude of N2-P2 and VAS. We revealed that taping along the forearm decreased pSEPs and subjective pain perception under the white-taping and elastic-taping conditions. The underlying mechanism of pain relief was the distraction effect in both taping conditions. In addition, elastic-taping with tension changes afferent inputs mainly from the skin, and this might more effectively decrease the subjective pain perception than that achieved under the white-taping condition.